THE EFFECT OF VARIATIONS SPEED OF THE CONDENSER FAN WITH CONTROL FREQUENCY INVERTER ON THE ICE SLUSH MACHINE APPLICATION - Muliawan, Rizki; Septyansah, Septyansah; Khakim, Nur; YP, Bowo; Falahuddin F, MA; Azmy, Ilham (AUSTENIT, 2022)
The condenser is one of the main components in the ice slush machine system that functions to removed heat from the system to the environment. In this system, the condenser is equipped with a fan whose rotation speed is modified using an inverter that aims to determine the system performance and condenser capacity at each fan rotation variation of the ice slush machine. There are 3 variations of frequency settings in this system 50 Hz, 40 Hz, and 30 Hz, with equivalent velocity air 3.6, 2.9, and 1.9 m/s respectively. In this study, the performance of the ice slush machine with various condenser fan speed settings was studied including, how long the product temperature is reached, condenser capacity, actual COP, efficiency, and electrical power. The test results show that the fastest product temperature is reached when using a fan speed setting of 1397 rpm, which is 145 minutes with a condenser capacity of 42.36 kW. The highest actual COP is obtained from the fan speed set at 1397 rpm of 2.58 with an efficiency of 57.5% and electrical power consumption of 269.64 W. The fan speed setting at 1090 rpm has a condenser capacity of 33.78 kW, COPactual of 2.46 with an efficiency of 56.2%, and electric power consumption of 272.09 W. The fan speed setting at 711 rpm has a condenser capacity of 21.73 kW, an actual CO of 2.15 with an efficiency of 49.2%, and electric power consumption of 312.71 W.